Evaluation of Drug–Drug Interactions of Rucaparib and CYP1A2, CYP2C9, CYP2C19, CYP3A, and P‐gp Substrates in Patients With an Advanced Solid Tumor. Issue 1 (20th December 2018) - Xiao, Jim J.; Nowak, Dorota; Ramlau, Rodryg; Tomaszewska‐Kiecana, Monika; Wysocki, Piotr J.; Isaacson, Jeff; Beltman, Jeri; Nash, Eileen; Kaczanowski, Robert; Arold, Gerhard; Watkins, Simon
Abstract : This phase I study (CO‐338‐044; NCT02740712), conducted in patients with advanced solid tumors, evaluated the effect of the poly(ADP‐ribose) polymerase (PARP) inhibitor rucaparib on the pharmacokinetics (PK) of caffeine 200 mg, warfarin 10 mg, omeprazole 40 mg, and midazolam 2 mg (cytochrome P450 (CYP) 1A2, CYP2C9, CYP2C19, and CYP3A substrates; dosed as a cocktail) and digoxin 0.25 mg (P‐glycoprotein (P‐gp) substrate; dosed separately) without rucaparib and following oral rucaparib 600 mg b.i.d. Geometric mean (GM) ratios (90% confidence interval (CI)) of area under the concentration‐time curve (AUC) from time zero to last quantifiable measurement with and without rucaparib were: caffeine, 2.26 (1.93–2.65); S‐warfarin, 1.49 (1.40–1.58); omeprazole, 1.55 (1.32–1.83); midazolam, 1.39 (1.14–1.68); and digoxin, 1.20 (1.12–1.29). There was limited effect on peak concentration of the substrates (GM ratios, 0.99–1.13). At steady state, rucaparib 600 mg b.i.d. moderately inhibited CYP1A2, weakly inhibited CYP2C9, CYP2C19, and CYP3A, and marginally increased digoxin exposure.